Analysis of multiple choice questions on the theme of growth and development of class III living creatures MI mainstay Ciamis - Nugraheni, Aninditya Sri; Badawi, Jami Ahmad; Abroto, Abroto; Sofia, Fifin (International Journal for Educational and Vocational Studies, 2022)
This study was conduct as an effort to improve the learning process and assessment in learning in elementary schools on the theme of health is important. The questions used by the teacher should be test for feasibility first to find out each item can be us to measure the competencies to be measure. This research was conduct with quantitative methods. The instrument used is multiple choice questions on the important health theme. Data analysis was performe using SPSS. The results showed that 92% of the questions were categorized as valid and 8% were categorized as invalid, with a high level of reliability with an R1 of 0.83, the level of difficulty of the questions with a percentage of 0%. Medium category questions with a percentage of 12%, questions in the easy category with a percentage of 88%. At the level of distinguishing power, there are 36% or as many as 9 questions in the category of good discriminating power, 48% or as many as 12 questions in the medium category and 16% or as many as 4 questions in the poor category. Meanwhile, the distractor function analysis shows that 16% of the distractors are functioning well, which are found in 4 items and 84% of the distractors are not functioning, which are spread over 21 items.